2017
DOI: 10.1097/iae.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Serum Insulin-Like Growth Factor I and Retinopathy of Prematurity

Abstract: INTRODUCTION Low serum insulin-like growth factor 1 (IGF-1) has been associated with development of severe retinopathy of prematurity (ROP), but no U.S. studies have been reported. We sought to determine the relationship between postnatal serum IGF-1 levels and severe ROP in a racially diverse U.S. cohort. METHODS Prospective cohort study of 74 infants with birth weight (BW) <1251g and a known ROP outcome at 3 Philadelphia hospitals. Weekly postnatal filter-paper bloodspot IGF-1 assays) were measured through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…It is well known that preterm infants who are at the highest risk for development of severe ROP are more likely to be growth suppressed. Poor growth and low systemic IGF-I levels have been shown to be important predictors of severe ROP [36,37]. The computerized clinical algorithm Weight, Insulin-like growth factor (IGF-1), Neonatal Retinopathy of Prematurity (WINROP) has been developed as a non-invasive tool for identifying infants at risk for ROP based on postnatal weight gain and IGF-I levels [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that preterm infants who are at the highest risk for development of severe ROP are more likely to be growth suppressed. Poor growth and low systemic IGF-I levels have been shown to be important predictors of severe ROP [36,37]. The computerized clinical algorithm Weight, Insulin-like growth factor (IGF-1), Neonatal Retinopathy of Prematurity (WINROP) has been developed as a non-invasive tool for identifying infants at risk for ROP based on postnatal weight gain and IGF-I levels [56].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I is a permissive factor for VEGF, and serum levels have been shown to be deficient in preterm infants who developed severe ROP [6,36,37]. Serum and vitreous fluid IGF-I levels at P14 and P21 are presented in Figure 7.…”
Section: Effect Of Bumetanide On Igf-1 Levelsmentioning
confidence: 99%
“…Studies have shown that low serum IGF‐1 is associated with development of severe ROP 48, 49, 50. IGF‐1 supplementation may be a treatment option to prevent the occlusion of vasculature during the first phase of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely preterm infants are at high risk of developing morbidities, including retinopathy of prematurity (ROP), a multifactorial disease with a complex pathogenesis that is not yet fully understood. We and others have identified low postnatal levels of IGF-I as a strong risk factor for ROP [13]. Other factors beyond low gestational age (GA) at birth and low postnatal levels of IGF-I that have been identified as risk factors for ROP include low birth weight and poor postnatal growth, sub-optimal oxygen therapy, depletion of the maternal supply of growth and nutritional factors, and red blood cell transfusion [1,46].…”
Section: Introductionmentioning
confidence: 99%